Don't You Feel Well, Sam? - Hest, Amy; Jeram, Anita (USA, 2002)
When Sam has cough, Mrs. Bear tends to him all through the cold night...
Keywords: Animal Story; Bears; Juvenile Fiction; Mother & Son - Sick Fiction